Improving Children's Fine Motor Skills Through Playing Plasticine at Raudhatul Athfal Al-Fajar - Nirwana Febriani Hasibuan; Ahmad Syukri Sitorus (Journal of Childhood Development, 2023)
This research aims to improve performance so that children's fine motor development can develop well. This research was conducted at RA Al Fajar located at Jln Jermal XV No. 5 Denai, Medan Denai District. This is a classroom action research implemented by researchers in the classroom using self-reflection. This research was conducted in the 2023/2024 school year, specifically in the even semester, involving 20 children as research subjects, consisting of 10 boys and 10 girls. The results showed that the use of plasticine in improving children's fine motor skills resulted in consistent and significant improvements from pre-cycle to cycle II, both in individual scores and class averages. The total score increased from 137 in pre-cycle to 169 in cycle I, and finally reached 374 in cycle II. The research makes a significant contribution in the development of fine motor skills in early childhood.  The research offers innovation in learning methods by introducing fun and interactive activities, which helps teachers find alternative teaching approaches that suit children's developmental needs.